PELATIHAN DAN PENDAMPINGAN DIGITISASI NASKAH LONTAR KOLEKSI MUSEUM LONTAR DUKUH PENABAN KABUPATEN KARANGASEM BALI - agus heru setiawan (Institut Seni Indonesia Surakarta, 2021)
AbstractThis article describes the process of training and mentoring transfer of lontar script media collections from the Oluseum Lontar Manuscripts at Dukuh Penaban Karangasem Bali into digital media carried out by the PKM ISI Surakarta team. The training and mentoring activities aim to support the pioneering development of an online information system carried out by the museum and further encourage the preservation of lontar manuscripts which are a medium for accommodating traditional Balinese knowledge. The focus of its activities is to provide training and mentoring to management staff and those appointed by the museum, so that they are skilled at mastering photographic techniques and appropriate technology as well as supporting software needed in the process of transferring lontar manuscripts into digital form. The target of this training is that the participants can independently transfer the lontar script media and use supporting software to prepare the results of the previous media transfer process into the form of an e-book file. The training methodology focuses on giving material orally, strengthening the material by doing hands-on practice and the mentoring process. As a result of its output, this training and mentoring activity was able to produce several digital files as well as the formation of e-books of lontar manuscripts from the collection of Dukuh Penaban Lontar Manuscripts Museum. Key words: digitisO. Dukuh Penaban, museum, lontar manuscript